Examining the Effects of Leadership, Market Orientation and Leader Member Exchange (LMX) on Organisational Performance - Lo, May-Chiun; Abang Azlan, Mohamad; T., Ramayah; Chai, Wang Yin (Kaunas University of Technology, 2015)
Based on the theory of customer value, comprehending the needs of customers and creating value for them is crucial for organisations to be competitive in the marketplace. Although there is an upward trend in the study of customer value, it is not known if the impact of leadership and market orientation on performance was researched in any studies. In this study, the concept of market orientation is comprised of three-dimensional constructs, while leadership consists of two-dimensional constructs. This study endeavours to investigate the constructs of market orientation, leadership and organisational performance in a single framework. To do so, a total of 184 financial services companies in Malaysia took part in this research. The analysis highlights that organisational performance was impacted by various components of market orientation. This paper further discusses the findings’ implications, limitation of the study and future research directions.